Introductory probability and statistics : applications for forestry and natural sciences - Mathai, A. M.; Kozak, Antal (Wallingford, UK : Cambridge, MA : CABI, 2008)
The book presents a calculus-based treatment of probability, concurrent and integrated with statistics through interactive tailored software applications designed to enhance the phenomena of probability and statistics. This work includes software programs and a CD-ROM containing the interactive software leading to the Statistical analysis.
Includes bibliographical references (p. 317-319) and index.
aia 30/8/17
Loans
Keywords: Probabilities --and computer simulation; Forests and forestry; Probabilities